Measurement characteristics and convergent validity of temporally modulated Gap–Overlap task versions: Evidence from an Eye-Tracking study in adolescents - Žunič, Dragana; Alimović, Sonja; Milić, Mladen; Žolgar Jerković, Ingrid (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Although the gap–overlap paradigm is widely used in eye-tracking research to investigate visual attention disengagement, methodological heterogeneity limits comparability across studies. Aim. This study aimed to examine the measurement characteristics and convergent validity of the two most commonly used versions of the gap–overlap task, and to evaluate the sensitivity and robustness of selected eye-movement and fixation-based indicators across experimental conditions. Methods. A quantitative, non-experimental design was employed in a normative sample of typically developing adolescents (N = 53; M = 13.98; SD = 0.93). Disengagement of visual attention was assessed using both longer and shorter versions of the gap–overlap task, with eye movements recorded by a Tobii Pro Nano eye tracker. Analysed indicators included performance level, temporal and fixation-based measures, and spatial gaze dispersion indices defined by distance percentiles under baseline (no-gap), gap, and overlap conditions. Results. The results showed moderate to very strong convergence between the longer and shorter task versions for most indicators. A robust gap effect was observed in both versions, with the shortest mean saccadic reaction times in the gap condition. Fixation-based and spatial gaze dispersion indices showed consistently high convergence across all experimental conditions, whereas temporal indicators showed greater variability, with weak convergence for mean saccadic reaction time in the overlap condition. Conclusion. Shortened gap–overlap tasks can provide valid estimates of visual attention disengagement when robust measurement indicators are used. Fixation-based and spatial dispersion metrics show strong convergent validity across task versions, supporting their use in developmental and applied research.